1984
DOI: 10.1039/c39840000736
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric synthesis of (–)-exo-brevicomin. Chirality transfer from a chiral (tetrahy-dropyranyloxyallyl)boronate in the condensation with aldehydes

Abstract: Chirality transfer from a chiral (y-tetrahydropyranyloxyal1yl)boronate is employed to secure the asymmetry in the synthesis of (-)-exo-brevicomin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1992
1992
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Selective conversions of the vinylic sulfoximines II and allylic sulfoximines III to the enantio‐ and diastereopure building blocks IV − VIII can be envisaged considering (i) the facile lithiation of vinylic sulfoximines4,13−17 and allylic sulfoximines2,5,11,12,18−24 at C‐α, (ii) the ready nickel‐catalyzed cross‐coupling reaction of vinylic sulfoximines with organometallics,4,15,25,26 (iii) the excellent Michael acceptor properties of vinylic sulfoximines and their (dialkylamino)sulfoxonium salts,27−30 (iv) the facile reduction of sulfoximines,31 (v) the ready S N reaction of allylic sulfoximines with copper organyls,5−7 (vi) the facile elimination of β‐hydroxy (dialkylamino)sulfoxonium salts under formation of epoxides,32,33 and (vii) the ready substitution of allylic sulfoximines 34. Thus, if attainable, sulfoximines II and III would be expected to considerably expand the range of synthetic possibilities available through the use of either enantio‐ and diastereopure homoallylic alcohols of types II and III bearing an alkyloxy group,35−42 a Cl atom,43−45 a (dialkylamino)carbonyloxy group,10e,46−51 or a silyl group52−54 instead of the sulfonimidoyl group, or by utilizing aldol‐type compounds55,56 and vinylic epoxides as starting materials 57. The feasibility of a synthesis of II from I was indicated by the work of Reggelin et al,11,12 who showed that lithium−titanium exchange using ClTi(O i Pr) 3 of lithiated allyl and crotyl sulfoximines bearing a chiral N ‐(silyloxy)alkyl group instead of the N ‐methyl group allowed their γ‐hydroxyalkylation under the highly regio‐ and diastereoselective formation of vinylic hydroxy sulfoximines of type II in medium to good yields 58.…”
Section: Introductionmentioning
confidence: 99%
“…Selective conversions of the vinylic sulfoximines II and allylic sulfoximines III to the enantio‐ and diastereopure building blocks IV − VIII can be envisaged considering (i) the facile lithiation of vinylic sulfoximines4,13−17 and allylic sulfoximines2,5,11,12,18−24 at C‐α, (ii) the ready nickel‐catalyzed cross‐coupling reaction of vinylic sulfoximines with organometallics,4,15,25,26 (iii) the excellent Michael acceptor properties of vinylic sulfoximines and their (dialkylamino)sulfoxonium salts,27−30 (iv) the facile reduction of sulfoximines,31 (v) the ready S N reaction of allylic sulfoximines with copper organyls,5−7 (vi) the facile elimination of β‐hydroxy (dialkylamino)sulfoxonium salts under formation of epoxides,32,33 and (vii) the ready substitution of allylic sulfoximines 34. Thus, if attainable, sulfoximines II and III would be expected to considerably expand the range of synthetic possibilities available through the use of either enantio‐ and diastereopure homoallylic alcohols of types II and III bearing an alkyloxy group,35−42 a Cl atom,43−45 a (dialkylamino)carbonyloxy group,10e,46−51 or a silyl group52−54 instead of the sulfonimidoyl group, or by utilizing aldol‐type compounds55,56 and vinylic epoxides as starting materials 57. The feasibility of a synthesis of II from I was indicated by the work of Reggelin et al,11,12 who showed that lithium−titanium exchange using ClTi(O i Pr) 3 of lithiated allyl and crotyl sulfoximines bearing a chiral N ‐(silyloxy)alkyl group instead of the N ‐methyl group allowed their γ‐hydroxyalkylation under the highly regio‐ and diastereoselective formation of vinylic hydroxy sulfoximines of type II in medium to good yields 58.…”
Section: Introductionmentioning
confidence: 99%
“…The anomeric carbon is necessarily chiral, its configuration can be controlled, and it provides a structural conduit for transmitting stereochemical information to the prochiral radical center. The nearest analogies that we could find for a THP-based chiral auxiliary for hydroxyalkyl radicals were the chiral γ-alkoxyallylboronates of Wuts and Hoffmann as well as the glycosylated dienes of Lubineau and Stoodley .…”
Section: Resultsmentioning
confidence: 93%
“…Adduct 23 is an intermediate in the synthesis of spirastrellolide A (Scheme 3). [51] The assumed transition states of these catalytic asymmetric allylation reactions are shown in Scheme 8. [44,45] The reaction of dodecanal with compound 22 in the presence of 2 mol % Zn(OH) 2 and 2.4 mol % ligand 9 proceeded smoothly to afford the corresponding chloroallylated adduct 24, which is the intermediate, in high yield with high diastereo-and enantioselectivities.…”
Section: Asymmetric Reactionsmentioning
confidence: 99%
“…It is noteworthy that the products are useful chiral synthons. [51] The assumed transition states of these catalytic asymmetric allylation reactions are shown in Scheme 8. We assumed a cyclic transition state of the chiral allylzinc species with an aldehyde, in which the aldehyde is activated by Zn.…”
Section: Asymmetric Reactionsmentioning
confidence: 99%